2014
DOI: 10.1074/jbc.m114.604009
|View full text |Cite
|
Sign up to set email alerts
|

Short Forms of Ste20-related Proline/Alanine-rich Kinase (SPAK) in the Kidney Are Created by Aspartyl Aminopeptidase (Dnpep)-mediated Proteolytic Cleavage

Abstract: Background: C-terminal SPAK fragments are found in kidney medulla. Results: We identified Dnpep as the protease responsible for SPAK cleavage, identified the sites of cleavage, and showed unusual preference for ␣ helices. Conclusion: C-terminal SPAK fragments originate from Dnpep-mediated proteolytic cleavage. Significance: SPAK and its cleavage are significant for the regulation of renal Na ϩ reabsorption and control of blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…We recently reported that the renal aspartyl aminopeptidase DNPEP exerts proteolytic cleavage activity against SPAK but not OSR1 (Markadieu et al. ). The sites of cleavage were located within the proline/alanine‐rich region but also within the kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the renal aspartyl aminopeptidase DNPEP exerts proteolytic cleavage activity against SPAK but not OSR1 (Markadieu et al. ). The sites of cleavage were located within the proline/alanine‐rich region but also within the kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports of SPAK protein expression in mice (McCormick et al, ; Simon, Nelson‐Williams, et al, ), we observed two prominent clusters of SPAK isoforms in mouse kidneys, including a cluster of large molecular weight isoforms running between 55 and 60 kDa, and smaller molecular weight isoforms closer to 45 kDa. The assignment of specific protein bands to specific mouse SPAK isoforms varies from study to study, but the general consensus remains that the larger molecular weight isoforms correspond to catalytically active SPAK, while the smaller molecular weight isoforms correspond to catalytically inactive SPAK in mice (Figure d) (Markadieu et al, ; McCormick et al, ; Simon, Nelson‐Williams, et al, ; Wade et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of these isoforms that have been discovered in the kidney differ from full length SPAK (~60kDa) in predicted molecular weight and kinase activity; the first isoform SPAK2 (~49kDa) is missing part of the N-lobe of the kinase domain and presumed to be kinase impaired, while the second isoform KS-SPAK (~34kDa) is solely kidney specific and kinase inactive as the entire kinase domain is missing [31]. Note that, as an alternative mechanism to the downstream promoter, the role of a protease has also been proposed as a mechanism for producing the short KS-SPAK isoform [77]. As the CCT domain is intact in these isoforms it is presumed that they compete with full length SPAK and OSR1 for RFxV docking sites, thus inhibiting CCC activity.…”
Section: Role Of Spak In Human Physiology and Diseasementioning
confidence: 99%